Stability indicating analytical method validation for hydralazine hydrochloride related substances method-I by Reverse Phase High Performance Liquid Chromatography in drug substances - Reddy, Swamy K.; Sharma, Pushpendra; Singh, Asheesh (Journal of Drug Delivery and Therapeutics, 2018)
A simple, rapid, precise, accurate and cost effective stability-indicating reversed phase (RP) HPLC related substance method-1 was validated for Hydralazine Hydrochloride (HYD HCl) in Active pharmaceutical ingredient. All the analytical parameters were determined as per ICH Q2B guidelines. Good chromatographic separation was achieved with Inertsil ODS 3V column (4.6 mm x 250 mm, 5 μm particle size) at a wavelength of 230 nm using phosphate buffer pH 2.5 and acetonitrile as mobile phase A and Methanol as mobile phase B with gradient programming with a flow rate of 1.0 ml/ min. The Resolution between Hydralazine peak and impurity-A should not be less than 3.0. From the statistical treatment of the linearity data of Hydralazine HCl, it is clear that the response of Hydralazine HCl is linear between 50 % to 150 % level. The correlation coefficient is greater than 0.998. The developed method showed good linearity, Accuracy, reproducibility, precision and robustness and can be suitably applied for the routine quality control analysis in the estimation of commercial formulations. Keywords: Hydralazine hydrochloride, HPLC, Validation, Estimation